1995
DOI: 10.1021/jm00021a015
|View full text |Cite
|
Sign up to set email alerts
|

N-Acylated .alpha.-Amino Acids as Novel Oral Delivery Agents for Proteins

Abstract: A series of N-acylated alpha-amino acids were synthesized and shown to improve the oral delivery of two protein drugs, salmon calcitonin (sCT) and interferon-alpha. Forty-five compounds in this series were tested in vivo in rats and primates. A significant positive correlation was found between the log P of the acylated amino acids and the decrease in serum calcium following oral dosage of sCT in rats. Such a correlation was not found for interferon-alpha. These derivatized amino acids only weakly inhibited th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…These compounds were designed as part of an effort to expand upon our earlier leads, which were N-acylated, R-amino acids. 16 Of the current compounds, 2 has been identified as a preclinical candidate (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…These compounds were designed as part of an effort to expand upon our earlier leads, which were N-acylated, R-amino acids. 16 Of the current compounds, 2 has been identified as a preclinical candidate (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…SAR testing indicated that lipophilicity [354] and hydrogen bonding [355] may play a role in intestinal permeation enhancement induced by Eligen®, although a consistent effect was not observed. A preliminary screen of 11 carriers showed that an optimal bell-shaped window of lipophilicity was required to improve oral heparin absorption [356].…”
Section: Peptide Hydrophobisationmentioning
confidence: 93%
“…3 Generally, penetration enhancers work by physiological alteration of the epithelium to exploit transport mechanisms. 66 Exploited transport mechanisms can be sub-grouped into methods that disrupt the structural integrity of the epithelial layer, decrease the mucous viscosity, open tight junctions or increase membrane fluidity. 3 Penetration enhancement principles assume a sufficient quantity of therapeutic agent and penetration enhancers at the site of absorption.…”
Section: Types Of Nanopreparationsmentioning
confidence: 99%